Survey of Breastfeeding and Colostrum knowledge and Practices Among Moroccan Women: a hospital-based study (Bangladesh Journal of Medical Science, 2024)
Objective In this study, our aim was to explore the knowledge and practice of breastfeeding and colostrum among Moroccan women. Material and methods this is a cross-sectional study. Data was collected from a sample of 100 Moroccan women through a 16-question questionnaire. Results and discussion The results revealed that a significant portion (74%) of the sample, had already made the decision to breastfeed before their pregnancies. Additionally, an overwhelming majority, 98% of the participants, fed their newborns with colostrum, reflecting a widespread acceptance and understanding of its importance with only a small minority opting for alternative feeding methods. Conclusion To promote better breastfeeding practices, it is crucial to address the knowledge gaps through targeted educational interventions that emphasize the importance of colostrum and provide accurate information particularly among women and expectant mothers.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1159-1167